IMPLEMENTASI PENGGUNAAN MEDIA LOOSE PARTS DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN ANAK 5-6 TAHUN - Amla, Amla; Miranda, Dian; Amalia, Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine theeimplementation of theeuse oflooseeparts media in improving the ability to count initially inchildren after 5-6 years in Haruniyah Islamic Kindergarten. Theresearch method utilized in conjunction with classroom actionresearch is descriptive. This class action research goes throughthe following stages, namely planning, implementation, action,observation and reflection. The results showed that the child'sinitial numeracy ability of indicators numbering objects 1 to 10by 87.5% was in the very good category, indicators sorted andpaired according to the number of objects 1 to 10 by 50% werein the category of quite good, indicators distinguished thenumber of lots and a few objects by 56.25% in the goodcategory, and the indicators stated the result of reducing objects 1to 10 by 62.5%. Based on the description above, it can beconcluded that through the implementation of the use of looseparts media in improving the ability to count initially in childrenaged 5-6 years, it can be said to be successful.